Accuracy Assessment of Azimuth, Elevation, and Time data resulted from using actual TLE and simulated-outdated TLE for tracking LAPAN-A2 Satellite - Setiawan, Joga Dharma; Ilham F, Muhammad Ario; Haryanto, Ismoyo; Muhida, Riza (ROTASI, 2023)
This study aims to assess the pointing accuracy of a directional antenna at a ground station using outdated Two-Line Element sets (TLEs) to track an equatorial Low-Earth Orbit (LEO) satellite, LAPAN-A2,  using AGI System Tool Kit (STK) software by analyzing the Azimuth, Elevation, and Time-lapse (AET). Simulations were performed using 1, 3, 6, and 12-month outdated TLEs.  Validation was successfully conducted at the initial work by comparing the orbital parameter data extracted from n2yo.com  to the STK simulation results using an updated TLE. It was found that maximum pointing errors using 1, 3, 6, and 12-month outdated TLEs, respectively, were: for the Azimuth 32º, 38º, 167º, and greater than 173º; for the Elevation: 5º, 8º, 7º, and greater than 73º; for the Time-lapse: 24, 35, 488, and 1052 seconds. It can be argued that the maximum pointing errors for up to the three-month outdated TLE are considered small such that a good communication quality between the ground station with a standard directional antenna could still be feasible. However the results of this study is limited only for a selected location in Central Java province in Indonesia. These findings have important implications for real-time satellite tracking when the ground station location becomes remote and disconnected from the internet network due to certain circumstances, such as natural disasters or other kinds of disruption, in which updating TLEs is not possible for a while.